2015
DOI: 10.1371/journal.pone.0115284
|View full text |Cite
|
Sign up to set email alerts
|

EMILIN2 Regulates Platelet Activation, Thrombus Formation, and Clot Retraction

Abstract: Thrombosis, like other cardiovascular diseases, has a strong genetic component, with largely unknown determinants. EMILIN2, Elastin Microfibril Interface Located Protein2, was identified as a candidate gene for thrombosis in mouse and human quantitative trait loci studies. EMILIN2 is expressed during cardiovascular development, on cardiac stem cells, and in heart tissue in animal models of heart disease. In humans, the EMILIN2 gene is located on the short arm of Chromosome 18, and patients with partial and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 39 publications
2
15
0
1
Order By: Relevance
“…29 and which is associated with the formation of elastic fibers. In line with this, patients with thoracic dissections had downregulated EMILIN-1, 30 possibly indicating that EMILIN-1 is important for intact elastic tissue.…”
Section: -supporting
confidence: 64%
“…29 and which is associated with the formation of elastic fibers. In line with this, patients with thoracic dissections had downregulated EMILIN-1, 30 possibly indicating that EMILIN-1 is important for intact elastic tissue.…”
Section: -supporting
confidence: 64%
“…It is also known that EMILIN2 is a binding partner of EMILIN1 [46]. Recently, it has been found that EMILIN2 regulates platelet activation, thrombus formation and clot retraction [47]. Hence, deficiency or reduction in EMILIN2 would impair platelet aggregation response.…”
Section: Resultsmentioning
confidence: 99%
“…Measurement of the auditory-evoked brainstem response, an indicator of overall auditory function, showed moderately elevated thresholds in Emilin2 −/− mice compared to +/+ mice for a click stimulus and a range of specific frequencies (8,16, and 32 kHz; fig. S3, B and C).…”
Section: Elevation Of Distortion Product Otoacoustic Emission and Audmentioning
confidence: 99%
“…Emilin 1 and emilin 2 can associate with microfibrils in skin extracts (13), and Emilin1-deficient mice display narrowing of blood vessels and hypertension (14). Emilin 2 has been reported to influence angiogenesis (15) and thrombosis (16), but its wider roles are unknown. The prominent expression of emilin 2 in the cochlea compared to other tissues (12) led us to investigate a specific role in frequency resolution.…”
Section: Introductionmentioning
confidence: 99%